HUBUNGAN ETOS KERJA, MOTIVASI DAN SIKAP INOVATIF DENGAN PENDAPATAN PETERNAK KERBAU DI KABUPATEN MANGGARAI BARAT - Nasrudin (Nasrudin); Endang Sulastri; I Gede Suparta Budisatria (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
The purposes of study was aimed to investigate the work ethics, motivations and innovative attitudes and its correlation with income of buffalo farmers in West Manggarai Regency. The surveys was conducted in December 2009until February 2010, involving 103 respondents chosen based on certain criteria. The relationships between work ethics, motivations and innovative attitude with the farmers income was analyzed using the chi-square, they are foundto have a significant correlation, and then continued by Phi test. The results showed that buffalo farmers in Lembor Subdistrict, West Manggarai regency, had a high working ethics, farming motivations and a positive innovativeattitude. The work ethics and innovative attitudes were not related to the income of buffalo farmers. The Breeding motivations had significantly correlated to income of buffalo breeder’s (X2count 14.934 > 3.84 X2table), meaning that thehigher breeding motivations, would bring effect to a higher income. The relationship between the variable of breeding motivations and the breeder’s income shows a medium (Phi coefficient = 0.381). The average income of respondents per livestock unit was Rp. 756,944 ± 221,542/year, while the average contribution from buffalo breeding activities for the household income, was 31.2%. This research implicated, that work ethics, and innovative attitudes, cannot be used to predict the farmers income, while breeding motivations, plays the role as a variable reliable to predict the farmers income.(Key words: Work ethics, Motivations, Innovative attitudes, Farmers income, Buffalo)